Teachers’ Effective Strategies in Reducing Students’ Anxiety in Speaking English - Andi Mar’ah Muthmainnah; Zul Astri; Inul Inul; Jumardi Jumardi; Novalia Tanasy; Nurul Fachrunnisa (GLENS: Global English Insights Journal, 2025)
This study explores the strategies used by English teachers to reduce students’ anxiety when speaking English in the classroom. Employing a qualitative approach, data were collected through semi-structured interviews with teachers and students at a junior high school. The findings reveal that students' speaking anxiety often stems from limited vocabulary, fear of making mistakes, and low self-confidence. To address these challenges, teachers implemented various strategies, including role-play activities, the use of dictionaries and digital pronunciation tools, interactive games, and emotional support through motivational feedback. These approaches helped create a supportive and engaging learning environment, encouraging students to participate more actively and confidently in speaking tasks. By tailoring instructional strategies to students’ needs and classroom conditions, teachers were able to foster a more positive attitude toward learning English. This study highlights the crucial role of effective teaching practices in mitigating language learning anxiety and offers practical insights for improving English-speaking skills among junior high school learners.